Real‐Time Observation of Diarylethene‐Based Photoswitches in a Cyclic Peptide Environment. Issue 6 (21st March 2019) - Schweigert, Caroline; Babii, Oleg; Afonin, Sergii; Schober, Tim; Leier, Julia; Michenfelder, Nadine C.; Komarov, Igor V.; Ulrich, Anne S.; Unterreiner, Andreas Neil
Abstract: We report the photophysical properties of diarylethene‐based photoswitches (DAE) which were incorporated into the backbones of macrocyclic peptides of variable sizes (6, 10 and 14 amino acids: cDAE‐6, cDAE‐10, and cDAE‐14). The insertion leads to a consistent bathochromic shift in UV/Vis absorption bands, a considerable peptide‐size‐dependent fluorescence intensity increase (up to a factor of 1.7), and a drastically reduced photoisomerization efficiency leading to formation of the ring‐closed DAE fragment. The compounds were studied by time‐resolved photoinduced broadband absorption spectroscopy, revealing a ring closure reaction for the unconstrained DAE reference system and, to a lesser extent, for cyclic cDAE‐14. The smallest cyclic peptide cDAE‐6 does not undergo any photoisomerization process at all. Furthermore, the DAE fragment ring closure reaction in the reference system is concurrent with intersystem crossing that is complete within a few picoseconds. Further analysis showed dominant triplet absorption throughout the observed spectral window (350–700 nm) in all macrocyclic systems. As a consequence, ring closure is favored in the unconstrained system in contrast to the cyclic peptides. Our studies demonstrate the importance of understanding the population dynamics of DAE rotamers when designing efficiently photocontrollable diarylethene‐based peptidomimetics. Abstract : Photoswitchable peptidomimetics : When incorporated into a peptidic macrocycle, the transient response of diarylethene (DAE) based photoswitches is dominated by the absorption contributions of triplet excited states. This results in a drastically decreased ring closure efficiency but increased fluorescence, both of which correlate with macrocycle size.